Knowledge acquisition for effective and efficient use of engineering software - Hawla, D L (Department of Electrical Engineering, 2023)
The problem of effective and efficient use of engineering software can be thought of as a Pareto optimal problem. However, the complexity of modern engineering software precludes the possibility of acquiring complete knowledge of the software's Pareto optimal set. Instead, heuristic knowledge must be acquired. The thesis proposes that heuristic knowledge be acquired via a knowledge acquisition procedure. The use of a knowledge acquisition system, which may be computerised, forms an integral part of this procedure. Two examples of knowledge acquisition illustrate the use of the knowledge acquisition procedure.